NEW CHALLENGES AND DEMANDS OF EDUCATION "SKILLS DEVELOPMENT" - Serna Huesca, Odete; Sánchez Serrano, Cinthia Jessica; Rubio Martínez, Isabel (Atenas, 2015)
Undoubtedly once we asked if we live in a time of change or a change of time and have been great revolutions product of globalization expressing a cycle of expansion that have impacted the political, social, economical in either time, cultural and other fields. Mexico in general and in particular the education system is not exempt to this impact, for which we have set great challenges; knowing how to educate this was also the teacher must also cope and adapt to the changes imposed by the changes.